2021
DOI: 10.12688/hrbopenres.13296.1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying interventions to improve hand hygiene compliance in the intensive care unit through co-design with stakeholders

Abstract: Background: Despite the effectiveness of hand hygiene (HH) for infection control, there is a lack of robust scientific data to guide how HH can be improved in intensive care units (ICUs).  The aim of this study is to use the literature, researcher, and stakeholder opinion to explicate potential interventions for improving HH compliance in the ICU, and provide an indication of the suitability of these interventions. Methods: A four-phase co-design study was designed. First, data from a previously completed syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The ABHR consumption remained still high in the second observation cycle and the model for ABHR trends were statistically significant. It has been shown that the ABHR availability at the point of care could influence the nurses' use of ABHR (Hansen et al, 2015 ; Lambe et al, 2021 ). Therefore, one reason for the high level of ABHR consumption in our study could be that, in this ICU, the hospital had positioned ABHR dispensers close to the patients many years prior to the study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ABHR consumption remained still high in the second observation cycle and the model for ABHR trends were statistically significant. It has been shown that the ABHR availability at the point of care could influence the nurses' use of ABHR (Hansen et al, 2015 ; Lambe et al, 2021 ). Therefore, one reason for the high level of ABHR consumption in our study could be that, in this ICU, the hospital had positioned ABHR dispensers close to the patients many years prior to the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Erasmus et al ( 2009 ) argued that a lack of positive role models and social norms might hinder HH compliance. Through strengthened competence, the IPLs could become role models for other personnel, which has proven to be an important issue in HH compliance (Lambe et al, 2021 ). The role of IPLs did not seem to have an influence on ABHR consumption or ICU‐HAI trends.…”
Section: Discussionmentioning
confidence: 99%
“…The results above raise several issues worthy of further discussion. Only 20% of participants thought that workers should be involved in the design of health messages despite the apparent value of stakeholder input being evidenced in the literature (Jenner et al, 2005; Lambe et al,2021). These findings suggest that there may be a recruitment challenge for any researchers/organization wishing to involve members of staff in the design of HH interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Lambe et al (2021), however, did conduct codesign tasks with stakeholders (including ranking and rating exercises) in a clinical setting and used findings to propose guidance for how HH initiatives can be constructed. Use of visual communication scored highly, and reprimands or coercive approaches were less favorably received.…”
Section: Theoretical and Academic Contextmentioning
confidence: 99%
See 1 more Smart Citation